The impact of corporate governance on the voluntary accounting information disclosure in Malaysian listed banks - Htay, Sheila Nu Nu (World Business Institute, 2012)
Financial accounting information is the main part of the annual reports on which investors rely. The reliability and relevance of the financial accounting information is on the shoulders of directors. It has been highlighted in the corporate governance literature that information disclosure about the companies is the heart of the good corporate governance system. In Malaysia, there is no research conducted to examine the relationship between corporate governance and voluntary accounting information disclosure although it is important to examine it. Therefore, the objective of this research is to investigate the impact of corporate governance on voluntary financial accounting information disclosure of Malaysian listed banks. The sample includes twelve listed banks on Bursa Malaysia from1996 until 2005. The findings of the panel data regression show that higher INE_BZ (at 1% Sig. level), lower DOWN (at 10% Sig. level) and higher BZ (at 5% Sig. level) have more voluntary financial accounting information disclosure. The other variables such as BLS, IOWN and BOWN are in line with hypotheses while BZ is not and the main reason for BZ not being in line with hypothesis is the sample firms already have optimal board structures.